2020
DOI: 10.1108/jkm-02-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

The big data-business strategy interconnection: a grand challenge for knowledge management. A review and future perspectives

Abstract: Purpose Designing knowledge management (KM) systems capable of transforming big data into information characterised by strategic value is a major challenge faced nowadays by firms in almost all industries. However, in the managerial field, big data is now mainly used to support operational activities while its strategic potential is still largely unexploited. Based on these considerations, this study proposes an overview of the literature regarding the relationship between big data and business strategy. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 89 publications
0
41
0
1
Order By: Relevance
“…Development is widely regarded as a means of achieving competitive advantage (Suoniemi et al 2020). Because of life circumstances and a constant need for continuous improvement in accordance with the needs and desires of the individual, scholars are primarily concerned with innovation (Ciampi et al 2020). Developments in all areas of life contribute to innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Development is widely regarded as a means of achieving competitive advantage (Suoniemi et al 2020). Because of life circumstances and a constant need for continuous improvement in accordance with the needs and desires of the individual, scholars are primarily concerned with innovation (Ciampi et al 2020). Developments in all areas of life contribute to innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to offer a non-biased and fine-grained analysis of the literature concerning the topic of SME default prediction, we opted for a hybrid approach combining a quantitative bibliometric analysis and a systematic literature review. This approach has already been adopted in other field of studies, such as sustainability (Mura et al 2018 ), innovation (Klarin 2019 ; Marzi et al 2021 ), knowledge management (Fakhar Manesh et al 2021 ; Pellegrini et al 2020 ), strategy (Ciampi et al 2020 ) and entrepreneurship (Delgado García et al 2015 ; Sassetti et al 2018 ), where it showed its effectiveness and reliability (Ding et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The review is based on: “The big data-business strategy interconnection: a grand challenge for knowledge management. A review and future perspectives,” by Ciampi et al (2020), published in Journal of Knowledge Management. To date, big data has been largely deployed to enhance operational activities.…”
Section: Commentmentioning
confidence: 99%